COATED TONGUE TREATMENT USING TONGUE SCRAPER ALL OVER THE SURFACE OF TONGUE DORSUM (PERAWATAN COATED TONGUE MENGGUNAKAN TONGUE SCRAPER PADA SELURUH PERMUKAAN DORSUM LIDAH) - Indah Puti R Sabirin; Mega Zhafarina (Fakultas Kedokteran Gigi Unjani, 2022)
A coated tongue is characterized by a white, yellowish-brown, or blackish-coloured coating on the tongue's surface. Coated tongues are formed from debris consisting of bacteria on the dorsal surface of the tongue, a large number of desquamated epithelial cells derived from the oral mucosa, leukocytes from periodontal pockets, and blood metabolites, and a variety of different nutrients. Score according to Gomez's justification to see the colour change in this case score one and Miyazaki classification to see the distribution of the spread of white plaque in the case of score 3. The treatment plan in this case provides medication in the form of chlorhexidine gluconate mouthwash 0.2% and an emphasis on maintaining oral hygiene and using tongue scraper aids. Patients were asked to do one week and five weeks of control to see the development of lesions in the form of white plaque. DOI : 10.54052/jhds.sd22.p177-184